Profiling of Phenolic Compounds Composition, Morphological Traits, and Antioxidant Activity of Miscanthus sacchariflorus L. Accessions - Bimal Kumar Ghimire; Erik J. Sacks; Seung Hyun Kim; Chang Yeon Yu; Ill Min Chung (Agronomy, 2021)
Miscanthus sacchariflorus is a potential source of sustainable biofuel and other bioactive compounds. The high adaptive range of M. sacchariflorus may cause variation in its morphological traits and phytochemical composition. Although some metabolites have been reported from M. sacchariflorus, little is known about its phenolic compound composition and antioxidant or oxidant properties. This study evaluated the morphological traits, antioxidant properties, and phenolic compound profile of M. sacchariflorus collected from various regions of China, Korea, Japan, and Russia. The antioxidant potential of the leaf extracts of various accessions of M. sacchariflorus was estimated by 1,1-diphenyl-2-picrylhydrazyl (DPPH) radical scavenging assay and 2,2′-azinobis 3-ethylbenzothiazoline-6-sulfonate (ABTS). An extensive study of the antioxidant activity and phenolic compounds of M. sacchariflorus obtained from different locations in four different countries could provide a comprehensive catalogue of the phytoconstituents and antioxidant properties of M. sacchariflorus accessions to consumers and nutraceutical industries. A total of 22 phenolic compounds were identified and quantified, among which p-coumaric acid, ferulic acid, p-hydroxybenzoic acid, chlorogenic acid, vitexin, and luteolin were the most dominant phytochemical compounds detected in the majority of the accessions. The antioxidant potential (DPPH) of the leaf extracts of all of the accessions ranged from 28.85 ± 1.53 µg mL−1 in MS-447 to 99.25 ± 1.63 µg mL−1 in MS-190. The antioxidant properties (ABTS) of the leaf extracts of all accessions ranged from 25.65 ± 2.06 in MS-258 to 83.62 ± 2.02 in MS-271. Pearson’s correlation analysis showed a significant and positive correlation between antioxidant activity and total phenolic content, and total flavonoid content varied widely among M. sacchariflorus accessions from the four geographical study regions. A strong and positive association was observed between DPPH with total phenolic content and total flavonoid content. Moderately positive correlations were observed between DPPH scavenging activity with gentisic acid, p-hydroxybenzoic acid, chlorogenic acid, p-coumaric acid, rutin, and quercetin (r = 0.385, r = 0.379, r = 0.362, r = 0.353, r = 0.490, and r = 0.372, respectively), suggesting that phenolic compounds are major contributors to the antioxidant potential of M. sacchariflorus. Thirty-two accessions collected from four different countries (China, Korea, Japan, and Russia) were characterized for 17 quantitative morphological traits. A wide range of diversity was observed in the morphological traits, with plant height ranging from 18.00 ± 1.00 cm to 163.20 ± 4.00 cm. Plant height was significantly correlated with biomass yield (fresh weight; r = 0.439, p < 0.05) and also had moderately positive correlations with culm length (r = 0.356, p < 0.05). Culm length was moderately correlated with the biomass yield fresh weight (r = 0.419*, p < 0.05) and the biomass yield dry weight (r = 0.425*, p < 0.05); however, it exhibited weak and negative correlations with compressed plant circumference (CCirc) (r = −0.374, p < 0.05) and total culm node number (TCmN) (r = −0.440, p < 0.05). Principal components analysis was performed to assess the variation in 17 morphological traits in 32 accessions of M. sacchariflorus. The first two principal components explained 51.24% of the morphological variations. A dendrogram generated from unweighted pair group method with arithmetic mean (UPGMA) clustering based on morphological characters was not found to be consistent with another dendrogram based on phytochemicals. In both cases, the number of studied accessions collected from different geographical regions grouped into two major groups. However, no clear correlation between these two different approaches was found. The substantial variation in the morphological traits, bioactive properties, and phenolic compounds among the accessions may provide useful information for breeding programs attempting to obtain M. sacchariflorus varieties with improved phenolic compounds traits and improved bioactive properties.